Penanganan Penyelundupan Manusia Di Wilayah Pesisir Provinsi Lampung - Dwi wahyu handayani; I Gede Sideman; Yuni Ratnasari (Andalas Journal of International Studies (AJIS), 2019)
Coastal Lampung is one of the areas visited by immigrant, the asylum seekers, before heading to the destination country. They come from Afghanistan, Bangladesh, Myanmar, Pakistan, Sudan, and Somalia. Immigrants left their home countries because of conflict and socio-economic conditions. The concept of maritime development must pay attention to the social security aspect of illegal immigrants, and people smuggling. The specific purpose of this study is to get a development model for cooperation in handling human smuggling in the Lampung Coastal Region. This study uses the Lani Kass formula regarding non traditional security threats. From the formula, the researcher will explain the descriptive qualitative method of three aspects, such as vulnerability, the intention of the foreigners’s arrival and state capabilities. The result of this study shows that there is already a model of cooperation for handling people smuggling in Lampung, including to reach the coastal areas. Inter-party cooperation coordinated by the Ministry of Political, Legal and Security Coordination involves up to the regional government. The efforts to handle people smuggling in Lampung was intense around 2008 and faded around 2015. There was a dependency from the part of the regional government on the central government's budget and programs, and cooperation initiated by the central government with international organizations such as IOM, UNHCR and the destination countries of the refugees. The increasing cases have not been responded to by the government with adequate regulation and handling efforts. Indonesia has not signed a refugee convention, also affects the absence of regional regulations regarding people smuggling. Key words: People Smuggling, Vulnerability, Intention, State Capabilities, Local Government